Receipt of thoracic radiation therapy and radiotherapy dose are correlated with outcomes in a retrospective study of three hundred and six patients with extensive stage small-cell lung cancer. Issue 2 (November 2017) - Li-Ming, Xu; Zhao, Lu-jun; Simone, Charles B.; Cheng, Chingyun; Kang, Minglei; Wang, Xin; Gong, Lin-Lin; Pang, Qing-Song; Wang, Jun; Yuan, Zhi-yong; Wang, Ping
Abstract: Background: The importance of the thoracic radiation therapy (TRT) dose has not been clearly defined in extensive stage small-cell lung cancer (ES-SCLC) and it is unclear whether improved TRT dose translates into a survival benefit. Methods: 306 patients with ES-SCLC were retrospectively reviewed, of which 170 received IMRT/CRT fractionation RT after ChT, and 136 received chemotherapy (ChT) alone. We adopted the time-adjusted BED (tBED) for effective dose fractionation calculation. Due to the nonrandomized nature of this study, we compared the ChT + RT with ChT groups that matched on possible confounding variables. Results: Patients achieved 2-year OS, PFS and LC rates of 19.7%, 10.7% and 28.4%, respectively. After propensity score matching, (113 cases for each group), the rates of OS, PFS and LC at 2 years were 21.4%, 7.7% and 34.5% for ChT + TRT, and 10.3% ( p < 0.001 ), 4.6% ( p < 0.001 ) and 6.3% for ChT only ( p < 0.001 ), respectively. Among propensity score matching patients, 56 cases for each group received the high dose (tBED > 50 Gy) TRT and received low dose (tBED ≤ 50 Gy) TRT. Two-year OS, PFS and LC rates were 32.3%, 15.3% and 47.1% for the high dose compared with 17.0% ( p < 0.001), 12.9% ( p = 0.097) and 34.7% ( p = 0.029) for low dose radiotherapy. Conclusions: TRT added to ChT improved ES-SCLC patient OS. High dose TRT improved OS over lower doses. Our results suggest that high-dose thoracic radiation therapy may be a reasonable consideration in select patients with ES-SCLC.